Farmer producer organisations: Innovative institutions for upliftment of small farmers - Nikam, Vinayak; Singh, Premlata; Ashok, Arathy; Kumar, Shiv (The Indian Journal of Agricultural Sciences, 2019)
Need of Farmer Producer Organizations (FPO) was felt to overcome the problems of unorganized small farmers who lack access to resources and services. FPOs emerged as an interface between small farmers and the external world by providing forward and backward linkages, giving them required voice, market access, bargaining power, economy of scale and better prices. Among different tangible and intangible benefits, marketing related benefits like access to different market channels, decrease in risk, decrease in transaction cost, economy of scale etc. were reported prominently by different studies. Some studies recommended formation of women FPO, as male dominance in mixed type of FPO reduces women’s chance of equal participation. Structure and organization of FPO vary from country to country depending upon the legal and policy framework of the country. Ability of FPO to create and maintain linkages outside is linked to success of the FPO in long run. Articulation of demand, service provision, capacity building and financing are the important Extension and Advisory functions performed by FPOs. Weakness related to organization and group dynamics featured prominently in many studies, which can be overcome by enabling policy, ethics, professionalism and linkages creation for success and sustenance of FPO.